The Impact of Labour Union Fragmentation on Service Delivery in The South African Public Sector - Rulashe, Tando; Jam, Ayanda (Universitas Airlangga, 2025)
Abstract This study examines the impact of increasing fragmentation among labor unions in South Africa’s public sector on the government’s capacity to deliver services effectively. Grounded in Conflict Theory and Agency Theory, the research employs a qualitative methodology, drawing on secondary data from government reports, union publications, and scholarly articles published over the past decade. The analysis utilizes thematic content coding to identify patterns related to service disruptions, organizational inefficiencies, and the erosion of public trust. The findings reveal that political fragmentation and inter-union competition are primary drivers of service disruptions, complicating collective bargaining processes and weakening institutional cohesion. Public sector employees frequently find themselves navigating competing union mandates, which contributes to diminished morale, demotivation, and the absence of a unified institutional direction. These tensions exacerbate strains in the relationship between the state and organized labor, thereby impeding efforts to improve service delivery. This study contributes to the literature by establishing a link between macro-level labor dynamics and micro-level service delivery outcomes, a nexus that remains relatively underexplored in public administration scholarship. It calls for more coordinated, depoliticized labor relations as a means to restore institutional effectiveness and rebuild public trust. Keywords: employee & employer relations; fragmentation; labour union; public administration; public sector strikes; service delivery. Abstrak Penelitian ini mengkaji dampak meningkatnya fragmentasi di antara serikat pekerja pada sektor publik di Afrika Selatan terhadap kapasitas pemerintah dalam memberikan layanan secara efektif. Berlandaskan Teori Konflik dan Teori Keagenan, penelitian ini menggunakan metode kualitatif dengan memanfaatkan data sekunder yang diperoleh dari laporan pemerintah, publikasi serikat pekerja, dan artikel ilmiah yang diterbitkan dalam satu dekade terakhir. Analisis dilakukan melalui pengkodean isi tematik untuk mengidentifikasi pola terkait gangguan layanan, inefisiensi organisasi, dan menurunnya kepercayaan publik. Hasil penelitian menunjukkan bahwa fragmentasi politik dan persaingan antarsesama serikat pekerja merupakan faktor utama penyebab gangguan layanan, yang memperumit proses perundingan bersama serta melemahkan kohesi institusional. Pegawai sektor publik kerap menghadapi mandat serikat pekerja yang saling bersaing, yang pada gilirannya menurunkan moral, memicu demotivasi, dan menciptakan ketiadaan arah institusional yang terpadu. Ketegangan ini memperburuk hubungan antara negara dan organisasi pekerja, sehingga menghambat upaya untuk meningkatkan kualitas pelayanan publik. Studi ini memberikan kontribusi pada literatur dengan menghubungkan dinamika ketenagakerjaan pada tingkat makro dengan konsekuensi pelayanan publik pada tingkat mikro, sebuah keterkaitan yang relatif jarang dieksplorasi dalam kajian administrasi publik. Penelitian ini mendorong terciptanya hubungan ketenagakerjaan yang lebih terkoordinasi dan terlepas dari kepentingan politik guna memulihkan efektivitas institusional dan membangun kembali kepercayaan publik. Kata kunci: hubungan karyawan & pemberi kerja; fragmentasi; serikat pekerja; administrasi publik; pemogokan sektor publik, penyampaian layanan.